Penerapan Bimbingan Kelompok dengan Metode Role Playing untuk Meningkatkan Keterampilan Berkomunikasi Siswa dengan Teman Sebaya di SD Inpres Panaikang 1 Kota Makassar - Sri Hastati (STKIP Andi Matappa Pangkep, 2021)
This study aims to describe the implementation of group guidance with the role play method to improve the students' communication skills with peers at SD Inpres Panaikang 1 Makassar. Which will examine the implementation of group guidance with the Role Play method to improve students' communication skills with peers at SD Inpres Panaikang 1 Makassar. The data analysis techniques used are descriptive analysis and t-test analysis. The results showed that based on the observations at the first meeting, 3 students were in the high category, 16 students were in the medium category, and 4 students were in the low category, and there were no students in the very high and very low categories. At the second meeting, there were 4 students in the very high category, 13 students in the high category, 6 students in the medium category, and there were no students in the low and very low categories. At the third meeting, student participation increased because there were 5 students in the very high category, 14 students in the high category and 4 students in the medium category.